If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3xsquare + -5x + 2 = 0 Reorder the terms: 2 + 3aeqrsux + -5x = 0 Solving 2 + 3aeqrsux + -5x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + 3aeqrsux + -2 + -5x = 0 + -2 Reorder the terms: 2 + -2 + 3aeqrsux + -5x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3aeqrsux + -5x = 0 + -2 3aeqrsux + -5x = 0 + -2 Combine like terms: 0 + -2 = -2 3aeqrsux + -5x = -2 Add '5x' to each side of the equation. 3aeqrsux + -5x + 5x = -2 + 5x Combine like terms: -5x + 5x = 0 3aeqrsux + 0 = -2 + 5x 3aeqrsux = -2 + 5x Divide each side by '3eqrsux'. a = -0.6666666667e-1q-1r-1s-1u-1x-1 + 1.666666667e-1q-1r-1s-1u-1 Simplifying a = -0.6666666667e-1q-1r-1s-1u-1x-1 + 1.666666667e-1q-1r-1s-1u-1 Reorder the terms: a = 1.666666667e-1q-1r-1s-1u-1 + -0.6666666667e-1q-1r-1s-1u-1x-1
| 2z^2-3=-z-2 | | Log(3)(3x-4)=2 | | 9cosx+6sinx=10 | | 2h=4.5 | | x/6=13/24 | | 3*x^2+4*x=5*(2*x+9) | | 9x*x-4x=2x-1 | | -b(4)+6(4)= | | -b+6y= | | 2x+2-2x-3=62 | | 3Y-2(Y+4)=Y+3 | | 20-15m=12-15m | | 4x*x-2x=6(2x-1) | | 0=3.6t^2-134t-750 | | 8y-6=5y+9 | | 3cosineT+0.5=0 | | 4x-15=x+9 | | 3cosT+0.5=0 | | 15xwhat=135 | | (2x+1)(2x+1)=4x*x-1 | | 20x+10xy-5y=2 | | 2/-18=18 | | 5x^2-121=0 | | 2x-ln(x^2)=0 | | 27=g/-32 | | 4x+21=0 | | 2(3x+5)=-2x+42 | | 37x-2x^2=100 | | S+7=-12 | | 6x=2y+10 | | 16x+29=0 | | -a-20=-3 |